The Nine-hued pheasant and the daughter-in-law of the poor: Raise of Consciousness in Women - Neupane, Shree Prasad (New Journey, 2024)
Violence against women is not a new subject-matter in Nepali literature. The Nepali drama Masan by Gopal Prasad Rimal, novels like Rupmati by Rudraraj Pandey and Samanantar Akash by Padmawati Singh and many other literary genres deal women’s predicament. Unlike other writers, Ahuti presents the problems of Nepali women differently. Ahuti encourages the women to react strongly against any domination and to revolt against violence. But in the poem, Ahuti makes Sanikanchhi revolt against the excessive domination in her family and becomes able to establish her position in society. The main problem of the study is to present how Ahuti has presented the present condition of Nepali women in society. This article is qualitative. So, narration, description, and comparison, are the tools to analyze, and interpret the data. It is found that the poem concerns the Nepali women’s problem. Women are mistreated in society. They are taken as the means of entertainment. The major character ’Sanikanchhi’ in the poem is the symbol of all the Nepali women.